Women patients's experiences with electronic medical records: a `Jeevan Yapan' perspective - Tandon, Ayushi (My University, 2025)
Information technology for the digitalization of health records (i.e. EMR) has been researched extensively for the past three decades. Our review revealed that patients play an important role in EMR use but their experiences are rarely problematized. We conducted an eight-month long ethnography involving 52 patient interviews and 31 direct observations of ambulatory consultation sessions within OB/GYN departments across four healthcare organizations. We find that women patients’ experiences with EMRs cannot be solely explained by biomedical concepts; they are intertwined with their everyday mundane experiences of living besides managing health needs. Findings reveal that current EMR design-in-use removes patients from the context of their everyday lives and communities, resulting in adverse digitalization. We labelled these everyday experiences using indigenous term ‘Jeevan Yapan’, which encapsulates lived realities, mundane activities, and mechanisms employed by individuals in navigating their daily lives. We conclude by calling on digital health researchers and practitioners to be sensitive to the ‘Jeevan Yapan’ of patients and create situated mechanisms of accountability to patient community while working in non-western contexts. We also provide design principles aligning with the ethos of Jeevan Yapan relevant to the design-in-use paradigm.
PUBLISHED
Keywords: Digital health design; electronic medical records; patient experience; indigenous; Digital Humanities; Inclusive Society; Digital Platform